Progression of pulmonary function and correlation with survival following stereotactic body radiotherapy of central and ultracentral lung tumors - Regnery, Sebastian; Eichkorn, Tanja; Weykamp, Fabian; Held, Thomas; Dinges, Lisa A.; Schunn, Fabian; Winter, Hauke; Thomas, Michael; Debus, Jürgen; El-Shafie, Rami; Adeberg, Sebastian; Hörner-Rieber, Juliane (Cancers, 2020)
Stereotactic body radiotherapy (SBRT) to central and ultracentral lung tumors carries a risk of excessive toxicity. This study analyzed changes in pulmonary function tests (PFT) and their correlation with overall survival (OS) in 107 patients following central (n = 62) or ultracentral (n = 45) lung SBRT. Ultracentral location was defined as planning target volume overlap with the proximal bronchial tree (PBT). Vital capacity (VC) (−0.3 l, absolute −9.4% of predicted, both p < 0.001) and forced expiratory volume in the first second (FEV1s) (−0.2 l, absolute −7.7% of predicted, both p < 0.001) significantly decreased following SBRT. Higher maximum dose to the PBT significantly correlated with a steeper decline in VC (p = 0.005) and FEV1s (p = 0.03) over time. Pronounced decline in FEV1s between 6 and 12 months (HR = 0.90, p = 0.006) and pronounced decline in VC between baseline and 12 months (HR = 0.95, p = 0.004) independently correlated with worse OS. Consequently, PFT presented a statistically significant albeit clinically mild decrease in lung volumes following central and ultracentral SBRT that correlated moderately with maximum dose to the PBT. Stronger decline in pulmonary function was associated with constrained survival, advocating consequent performance of PFT during follow-up.
Gesehen am 25.11.2020